Cover Image, Volume 176A, Number 4, April 2018. Issue 4 (25th March 2018) - Zarate, Yuri A.; Smith‐Hicks, Constance L.; Greene, Carol; Abbott, Mary‐Alice; Siu, Victoria M.; Calhoun, Amy R. U. L.; Pandya, Arti; Li, Chumei; Sellars, Elizabeth A.; Kaylor, Julie; Bosanko, Katherine; Kalsner, Louisa; et al.
Abstract : The cover image, by Yuri A. Zarate et al., is based on the Original Article Natural history and genotype‐phenotype correlations in 72 individuals with SATB2‐associated syndrome, DOI: 10.1002/ajmg.a.38630